Metal-framework degradation reactions of the mixed-metal cluster anions [M3Ir(CO)(13)](-) (M=Ru, Os) with bis(diphenylphosphino)methane and with tricyclohexylphosphine: synthesis and structure of HRu2Ir(CO)(5)(dppm)(3), HRu2Ir(CO)(6)(PCy3)(3), H2Os2Ir2(CO)(10)(PCy3)(2) and H3Os3Ir(CO)(8)(PCy3)(3) - Haak, Susanne; Süss-Fink, Georg; Neels, Antonia; Stoeckli-Evans, Helen (My University, 1999)
The mixed-metal cluster anions [M3Ir(CO)(13)](-) (M=Ru, Os) react in methanol under metal-framework degradation with bis(diphenylphosphino)methane (dppm) or tricyclohexylphosphine (PCy3) to give a series of neutral tri- and tetranuclear mixed-metal clusters. The reaction of [M3Ir(CO)(13)](-) (M=Ru, Os) with dppm leads to the phosphine-substituted hydrido derivatives HRu2Ir(CO)(5)(dppm)(3) (1) and HOs2Ir(CO)(5)(dppm), (2), respectively. The two 48e clusters show a triangular arrangement of the M2Ir skeleton. The dppm ligands are coordinated in bridging positions over each metal-metal edge; the hydride is bonded terminally to the iridium atom. Cluster degradation is also observed by treating [Ru3Ir(CO)(13)](-) with PCy3 in methanol, giving the highly electron-deficient (44e) mixed-metal cluster HRu2Ir(CO)(6)(PCy3)(3) (3). The reaction of the osmium homologue [Os3Ir(CO)(13)](-) with PCy3 under the same conditions leads to a mixture of the neutral tetranuclear clusters H2Os2Ir2(CO)(10)(PCy3)(2) (4) and H3Os3Ir(CO)(8)(PCy3)(3) (5). Both clusters, 4 and 5 still have a tetrahedral metal core like the starting cluster anion but in 4 an osmium atom has been replaced by an iridium atom. The molecular structures of 1, 3, 4 and 5 were confirmed by single-crystal X-ray structure analyses. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: mixed-metal clusters; ruthenium; osmium; iridium; phosphine; RAY CRYSTAL-STRUCTURES; REACTIVITY; FLUXIONALITY